Reconstruction Of The Expansion Of Criminal Sanctions For Money Laundering Crimes Through Non-Conviction Based (Ncb) Asset Forfeiture And In Rem Lawsuit - Dhumilah, Dewic Sri Ratnaning; Mustofa, Muhammad; Shodiq, Md. (Pelopor Publikasi Akademika, 2025)
The construction of criminal sanctions for money laundering (TPPU) in Indonesia is still a classic problem that has not been successful. The dependence on proof of the original crime in the criminal process is often the main obstacle in its enforcement. This is compounded by the weakness of legal norms related to the process of confiscating assets resulting from money laundering. Data from the 2021 PPATK National Risk Assessment (NRA) report, the estimated value of the proceeds of crime reached IDR 44,200,000,000,000 (forty-four trillion two hundred billion rupiah) and has not been confiscated by the state. The results of the PPATK analysis also stated that the length of the TPPU criminal justice process was a factor. The procedure for criminalizing money laundering only focuses on fulfilling the elements of the crime while the object of the crime has always not received attention and has not been a special consideration as the main door to arresting the perpetrators of the crime even though there are indications of improper acquisition of assets. In Australia and America, the TPPU criminal process uses a combined criminal and civil system, namely through the in rem lawsuit method in the NCB concept which can be the main door in enforcing TPPU. The use of the in rem method in enforcing TPPU does not only focus on the purpose of